2013
DOI: 10.1111/bph.12133
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane protects against ethanol‐induced oxidative stress and apoptosis in neural crest cells by the induction of Nrf2‐mediated antioxidant response

Abstract: BACKGROUND AND PURPOSENuclear factor erythroid 2-related factor (Nrf2) is a transcription factor that up-regulates a diverse array of antioxidant genes and protects cells from oxidative damage. This study is designed to determine whether D-L-sulforaphane (SFN) can protect neural crest cells (NCCs), an ethanol-sensitive cell population implicated in fetal alcohol spectrum disorders, against ethanolinduced apoptosis and whether protective effects of SFN are mediated by the induction of Nrf2-mediated antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
68
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 54 publications
6
68
0
Order By: Relevance
“…It has been reported that sulforaphane functions as an antioxidant in skin and neural tissue (Kleszczynski et al, 2013;Chen et al, 2013). Moreover, anticancer potential of sulforaphane by suppressing cancer cell proliferation has also been well documented in breast, prostate and colon cancer cells (Johnston et al, 2004;Frydoonfar et al, 2004;HermanAntosiewicz et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported that sulforaphane functions as an antioxidant in skin and neural tissue (Kleszczynski et al, 2013;Chen et al, 2013). Moreover, anticancer potential of sulforaphane by suppressing cancer cell proliferation has also been well documented in breast, prostate and colon cancer cells (Johnston et al, 2004;Frydoonfar et al, 2004;HermanAntosiewicz et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…A similar release of Nrf2 from the gatekeeper complex is produced by the binding of sulforaphane to the complex [4,26,27,[46][47][48]. Following its release, free Nrf2 undergoes translocation to the nucleus where it accumulates and forms complexes with small transcription factors (such as the v-maf avian musculoaponeurotic fibrosarcoma oncogene homolog; Maf) that bind to the genomic antioxidant response element (ARE), activating the expression of both phase 2 detoxification systems and the complete armamentarium of endogenous antioxidant enzymes [4,26,27,36,[46][47][48][49][50][51][52][53][54][55][56].…”
mentioning
confidence: 99%
“…Nrf2 activation and the indirect antioxidant effects of sulforaphane appear to be ubiquitous; they have been observed in the liver [30][31][32]41,59,60], kidney [60], lungs [60][61][62][63], lens [58], central nervous system [49,60], immune system [50], choroid plexus [51], small intestine [9], large intestine [60], prostate [60], retinal pigment epithelial cells [34,39,64], corneal epithelial cells [55], astroglial cells [54], fetal neural crest cells [52], neuroblastoma cells [36], insulin-secreting pancreatic cells [65], differentiated peripheral blood neutrophils [53], endothelial cells [40], osteoblasts [37], and keratinocytes [33][34][35].…”
mentioning
confidence: 99%
“…Sulforaphane may prevent diabetic auric damage and cardiomyopathy by increasing Nrf2 activation in mice [104,105]. Sulforaphane showed protective effect against ethanol-induced oxidative stresses and apoptosis in neural crest cells by generating an antioxidant response with Nrf2 activation [106]. Sulforaphane activates the Nrf2/ARE pathway and inhibits 3-nitropropionic acidinduced toxicity in striatal cells by inhibiting MAPKs and NF-κB pathways [107].…”
Section: Sulforaphanementioning
confidence: 99%